2014
DOI: 10.1136/gutjnl-2014-307263.297
|View full text |Cite
|
Sign up to set email alerts
|

PWE-037 Panenteric Capsule Endoscopy: An Alternative Non-invasive Tool To Screen For Idiopathic Inflammatory Bowel Disease (ibd)

Abstract: complications (bleeding/pain) were analysed. Pearson chisquare tests were used to compare experiences by gender, high vs. low levels of socioeconomic deprivation (using Index of Multiple Deprivation scores), and whether patients reported receiving sedation or not. Results After excluding patients outside the target date range and those who did not have colonoscopy, 76,717 patients were eligible for analysis, of whom 60,581 (79.0%) responded to the questionnaire. Nearly all patients felt they understood the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…To date, five studies have evaluated the performance of CCE‐2 with ileo‐colonoscopy or small bowel CE in suspected or confirmed CD (Table ). There are also studies that evaluated the role of CCE in routine clinical practice without comparing with a reference standard, in postoperative CD, and in CD patients who refused or had incomplete colonoscopy . The first multicenter European study has reported that CCE‐2 has a comparable sensitivity of 86% but a low specificity of 40% for ileo‐colonic ulceration in active CD .…”
Section: Cce In CDmentioning
confidence: 99%
“…To date, five studies have evaluated the performance of CCE‐2 with ileo‐colonoscopy or small bowel CE in suspected or confirmed CD (Table ). There are also studies that evaluated the role of CCE in routine clinical practice without comparing with a reference standard, in postoperative CD, and in CD patients who refused or had incomplete colonoscopy . The first multicenter European study has reported that CCE‐2 has a comparable sensitivity of 86% but a low specificity of 40% for ileo‐colonic ulceration in active CD .…”
Section: Cce In CDmentioning
confidence: 99%